Imbibition phases and germination response of Mimosa bimucronata (Fabaceae: Mimosoideae) to water submersion - Kestring, Debora [UNESP]; Klein, Jeferson [UNESP]; Candido Ribeiro de Menezes, Luciana Cristina [UNESP]; Rossi, Marcelo Nogueira (Elsevier B.V., 2009)
Mimosa bimucronota is a pioneering tree that occurs predominantly in moist lowlands, floodplains and on margins of rivers and lakes in Latin America. The effect of submergence on seed germination in M. bimucronata was firstly studied. Patterns of water absorption by M. bimucronata seeds were investigated thereafter to assess the imbibition phases of scarified and unscarified seeds. The germination percentage was significantly higher in scarified than in unscarified seeds, and the velocity of seed germination also increased considerably in scarified seeds. Submergence duration did not significantly affect germination percentages of scarified and unscarified seeds. Therefore, seed viability after submersion suggests that M. bimucronata may display hydrochorous dispersal and also that seeds are able to germinate successfully in areas with frequent seasonal flooding. With respect to imbibition phases, phase II was very short or even absent for scarified and unscarified seeds; therefore, a plateau, where water absorption by seeds is established, was not observed. Finally, we verified that the passage from phase I to III was very tenuous and took a long time in seeds without scarification. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Germination; Mimosa bimucronata; Flooding; Imbibition phases; Dispersal